Growth of titanium dioxide nanorod over shape memory material using chemical vapor deposition for energy conversion application. (2020) - Khanna, Sakshum; Utsav,; Patel, Roma; Marathey, Priyanka; Chaudari, Rakesh; Vora, Jay; Banerjee, Rupak; Ray, Abhijit; Mukhopadhyay, Indrajit
Abstract: Nanostructured TiO2 demonstrates exceptional electrical and optical property which has attracted the researchers' attention in energy conversion and storage research. In the current study, we report the development of Titanium Dioxide nanorods (TiO2 NRs) rutile phase on NiTi alloy using a chemical vapor deposition technique. Systematic studies were performed for different camphor quantity (ranging from 3 mg to 7 mg) along with a constant substrate temperature at 950 °C. TiO2 NRs formation at a particular substrate temperature, controlled by the solid camphor precursor, results in dominant rutile phases of TiO2 within the nanorods (NRs) which was confirmed from X-ray diffraction. Off-normal growth with varying rod diameter and efficient photocatalytic properties are characteristics of these NRs prepared with the proposed method. Field-effect scanning electron microscopy (FE-SEM) revealed TiO2 NRs with exceptionally long length and diameter of 5–7 µm and 60–100 nm, respectively. The presence of oxygen in the camphor under argon and hydrogen atmosphere and assisted by nickel, results in thinning and elongation of the NRs. The resulting TiO2 NRs exhibited high crystallinity and large surface areas with high refractive Index, which is one of the promising materials for energy conversion applications.